2018
DOI: 10.1002/ase.1841
|View full text |Cite
|
Sign up to set email alerts
|

Acquiring Clinical Knowledge from an Online Video Platform: A Randomized Controlled Experiment on the Relevance of Integrating Anatomical Information and Clinical Practice

Abstract: Basic subjects in medical education, such as anatomy, are often taught through teaching formats that do not always sufficiently demonstrate the relevance of this basic information for clinical practice. Accordingly, it is a recent trend in anatomy education to link anatomical information more explicitly to clinical practice. This article presents an online video platform (Tuebingen's Sectio Chirurgica [TSC]) as one means of explicitly integrating preclinical anatomical knowledge and clinical application. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…At the same time, however, this is a pity, because social settings are of course also very important for medical training [121]. This applies, for example, to the field of doctor-patient communication [122,123] or to inter-professional cooperation [124]. Computers & Education is additionally interested in field studies with interventions in designs with pre-and post-tests of individual learners or control groups to compare digital vs. non-digital learning environments.…”
Section: Limitationsmentioning
confidence: 99%
“…At the same time, however, this is a pity, because social settings are of course also very important for medical training [121]. This applies, for example, to the field of doctor-patient communication [122,123] or to inter-professional cooperation [124]. Computers & Education is additionally interested in field studies with interventions in designs with pre-and post-tests of individual learners or control groups to compare digital vs. non-digital learning environments.…”
Section: Limitationsmentioning
confidence: 99%
“…Such experiences also open new perspectives for learners at all levels (43). A previous study (31) found that the acquisition of clinical knowledge was mediated by the entertainment aspect of a video. In the study presented here we also found that participants in the inter-professional condition learned more than the participants in the mono-professional condition.…”
Section: Discussionmentioning
confidence: 93%
“…51 Such experiences also open new perspectives for learners at all levels. 52 A previous study 38 found that the acquisition of clinical knowledge was mediated by the entertainment aspect of a video. In the study presented here we also found that participants in the inter-professional condition learned more than the participants in the mono-professional condition.…”
Section: Discussionmentioning
confidence: 98%